Development of a database structure for the first Geomorphological map of Greece at 1:1,000,000 scale - Alexandra Zervakou; Alexandros Petropoulos; Niki Evelpidou; Eirini Zananiri; Giannis Saitis; Evangelos Spyrou; Dionysios Goutis; Hampik Maroukian (European Journal of Geography)
Geomorphological maps offer researchers multiple advantages when studying an area, as they can provide insights into the formation processes of the observed landforms, as well as their possible evolution in the future. The geodatabase seems to be of primary importance, as it determines the way in which the data will be organized and presented on a map, and thus the map’s functionality. There are not specific guidelines for a database for geomorphological maps, as this would be dependent, inter alia, on the scale of the maps. However, up to this day, there is not a single data base template to be used for geomorphological mapping. In each case, the cartographer/geomorphologist determines the number of fields their layers will have and their type, as well as what information they will contain, depending on the scale they are working on, the variety of landforms of their area, the time and resources available (correspondingly, the accuracy their map will have) and the purpose of its creation. Also, while several countries - not only large ones, but smaller ones as well - do have a geomorphological map at national scale, many countries, Greece among them, do not. On the contrary, only parts of them have been mapped by various researchers, who did not share any common database, which renders the combination of the individual maps difficult. But even in countries with existent national geomorphological maps, a specific and common geodatabase structure was not followed. In this way, there is no uniformity in the data and comparisons between maps, as well as combinations of data are very difficult and require a lot of work. Therefore, as we have initiated a project to create the geomorphological map of the Greek territory at 1:1,000,000 scale, we found that, prior to the beginning of the mapping, it was imperative to create a geodatabase template which we intend to follow, and which can be used as a template for geomorphological mapping at national scale by other countries (researchers and/or authorities). Thus, in this paper, we propose a database template to be used in geomorphological mapping at global scale globally, so that the data and structure of maps share common properties, thus allowing for comparisons and combinations of data where necessary.